Mapping QTLs for aluminum tolerance in maize - Ninamango-Cardenas, F. E.; Guimaraes, C. T.; Martins, P. R.; Parentoni, S. N.; Carneiro, N. P.; Lopes, M. A.; Moro, JR; Paiva, E. (Kluwer Academic Publ, 2003)
Aluminum toxicity is one of the major constraints for plant development in acid soils, limiting food production in many countries. Cultivars genetically adapted to acid soils may offer an environmental compatible solution, providing a sustainable agriculture system. The aim of this work was to identify genomic regions associated with Al tolerance in maize, and to quantify the genetic effects on the phenotypic variation. A population of 168 F-3:4 families derived from a cross between two contrasting maize inbred lines for Al tolerance was evaluated using the NSRL and RSRL parameters in nutrient solution containing toxic level of aluminum. Variance analyses indicated that the NSRL was the most reliable phenotypic index to measure Al tolerance in the population, being used for further QTL mapping analysis. RFLP and SSR markers were selected for bulked segregant analysis, and additional SSR markers, flanking the polymorphisms of interest, were chosen in order to saturate the putative target regions. Seven linkage groups were constructed using 17 RFLP and 34 SSR markers. Five QTLs were mapped on chromosomes 2, 6 and 8, explaining 60% of the phenotypic variation. QTL(4) and marker umc043 were located on chromosomes 8 and 5, close to genes encoding for enzymes involved in the organic acids synthesis pathways, a widely proposed mechanism for Al tolerance in plants. QTL(2) was mapped in the same region as Alm2, also associated with Al tolerance in maize. In addition, dominant and additive effects were important in the control of this trait in maize.
Keywords: aluminum tolerance; linkage map; maize; quantitative trait loci; RFLP; SSR